Study of quality models used by logistics operators in Argentina and South America - Kadener, Lucas; Repetto, Horacio Andrés; Libertella, Ana María Lopez; Moltedo, Constanza (Technology audit and production reserves, 2023)
This research aims to gather information on the use of Excellence models (such as the Quality Awards) by Logistics Operators in Argentina and neighboring countries. Therefore, the object of the research is the quality models used by logistics operators. In general, these organizations, and mainly those where Logistics is their main service, have begun applying quality standards later than other types of organizations, like those in the manufacture or services industries. This is because their practice is not deemed an added-value activity by the customer. This study found that, at the regional level, these companies are in the process of applying Quality, Environmental, Road Safety and other Management Systems from the ISO suite (ISO 9001, ISO 14001, ISO 39001, etc.), but the use of Excellence models is only present in some, mainly in Argentina-based companies. Remarkably, this behavior does not replicate in other countries of the region (Brazil, Chile, Uruguay), where the aforementioned standards are more widely applied. On the other hand, some countries have their own standards (Argentina, Brazil) for Freight activities developed by their local chambers, but these are mainly focused on the operational aspect of their activity. In this study, information was collected regarding the methodology related to quality and excellence of 109 companies, belonging to Argentina, Brazil, Chile, Colombia and Peru. At the regional level, the ISO 9001 management model is adopted by 68 % of the organizations studied, followed by ISO 14001 adopted by 30 % of the organizations and ISO 45001 adopted by 15 % of the organizations. Based on the conclusions of this work, there is an opportunity to create specific policy around Quality Models for this industry that will support the creation of new standards and the improvement of existing ones. This paper can serve as a starting point for analyzing the scenario in other regions within a framework of similar geographical characteristics.